The landscape of Block-based programming: Characteristics of block-based environments and how they support the transition to text-based programming - Lin, Yuhan; Weintrop, David (Journal of computer languages (Online), 2021)
Block-based programming (BBP) environments have become increasingly commonplace computer science education. Despite a rapidly expanding ecosystem of BBP environments, text-based languages remain the dominant programming paradigm, motivating the transition from BBP to text-based programming (TBP). Support students in transitioning from BBP to TBP is an important and open design question. This work identifies 101 unique BBP environments, analyzes the 46 of them and identifies different design approaches used to support the transition to TBP. The contribution of this work is to provide a snapshot of the current state of BBP environments and how they support learners in transitioning to TBP.